2013
DOI: 10.1177/1535370212473704
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic complications in pregnancy: is resveratrol a solution?

Abstract: Diabetes is a metabolic disorder that, during pregnancy, may affect fetal development. Fetal outcome depends on the type of diabetes present, the concentration of blood glucose and the extent of fetal exposure to elevated or frequently fluctuating glucose concentrations. The result of some diabetic pregnancies will be embryonic developmental abnormalities, a condition referred to as diabetic embryopathy. Tight glycemic control in type 1 diabetes during pregnancy using insulin therapy together with folic acid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 108 publications
(143 reference statements)
1
33
0
1
Order By: Relevance
“…Resveratrol has been in use since ancient times as an Indian herbal preparation termed 'Darakchasava', which is derived from fermented grapes. Remarkably, the effects described for Darakchasava more than 4500 years ago (Singh et al, 2013) are the same described for resveratrol today. Today, Darakchasava is produced by several pharmaceutical companies and contains about 1.3-6.0 mg/L resveratrol (Paul et al, 1999).…”
Section: Structure and History Of Resveratrolsupporting
confidence: 56%
See 3 more Smart Citations
“…Resveratrol has been in use since ancient times as an Indian herbal preparation termed 'Darakchasava', which is derived from fermented grapes. Remarkably, the effects described for Darakchasava more than 4500 years ago (Singh et al, 2013) are the same described for resveratrol today. Today, Darakchasava is produced by several pharmaceutical companies and contains about 1.3-6.0 mg/L resveratrol (Paul et al, 1999).…”
Section: Structure and History Of Resveratrolsupporting
confidence: 56%
“…The glucuronide-and sulfate-conjugated metabolites of resveratrol peaked in plasma at 30-60 min post-administration, with a plasma half-life of 9.2 h. (Walle et al, 2004). In contrast, only small amounts of unmodified resveratrol (<5 ng/mL) were detected in plasma in a similar timeframe (Singh et al, 2013). In another study conducted on mice, rats, and humans, it was shown that within 24 h after administration of 0.03 mg/kg body weight (BW) resveratrol, nearly 50% of the resveratrol was excreted in the urine.…”
Section: Bioavailability Of Resveratrol and Plasma Levelsmentioning
confidence: 96%
See 2 more Smart Citations
“…Resveratrol administered to the dam has been detected in fetal plasma in rodents, but no data exists in humans. A recent review examined the possibility of using resveratrol for complications of diabetic pregnancy and reports a reduction in maternal glucose, cholesterol, and triglycerides, as well as a reduction in neural tube defects, in rodent models of diabetic pregnancy (57). Human pregnancy studies have not yet been undertaken.…”
Section: Resveratrolmentioning
confidence: 99%